Prevalence of Urinary Incontinence and Lower Urinary Tract Symptoms in School-Age Children - Akil, Ipek Ozunan; Ozmen, Dilek; Cetinkaya, Aynur Cakmakci (Urology Journal, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> Abstract Purpose: To investigate the prevalence of lower urinary tract symptoms (LUTS) and urinary incontinence (UI) in elementary school aged children in Manisa. Materials and Methods: Dysfunctional Voiding and Incontinence Scoring System (DVIS) which was developed in Turkey is used. A total of 416 children, 216 (51.9%) male and 200 (48.1%) female were recruited in this study. Results: Mean age of children was 10.35 ± 2.44 years (median10 years). Daytime UI frequency was 6.7% (28 child), nocturnal incontinence 16.6% (69 child) and combined daytime and nocturnal incontinence 4.1% (17 child). There was no statistically significant difference in the prevalence of nocturnal and or daytime UI between male and female gender. Mean DVIS score was 2.65 ± 3.95 and gender did not affect total DVIS points. The mean ages of achieving daytime bowel and bladder control were all significantly correlated with DVIS points. DVIS points were positively correlated with the history of UI of the family. Total points were increased when the father was unemployed. Conclusion: UI negatively influences health related quality of life of the family and child, so it is important that awareness of the UI and symptoms of lower urinary tract dysfunction. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Normal Tablo"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->